2007
DOI: 10.1111/j.1365-2516.2007.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term major joint outcomes in young adults with haemophilia: interim data from the HGDS

Abstract: A study of major joint outcomes, specifically range of motion and synovitis, was conducted with data from a subset of adolescents enrolled in the prospective Hemophilia Growth and Development Study (HGDS). Clinical observations were carried out over a 7-year period from 1989 to 1996. A secondary aim was to gain insight into factors that might influence decisions regarding maintaining or discontinuing prophylaxis during early adulthood. Twenty-nine participants (median age 17.4 at entry) were included. Median f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…In our study, higher MRI scores for the maximally affected ankle compared with the mean index joint in all patient subgroups and the scarcity of pathologic findings in knees of patients with normal ankles indicate that in most patients, the ankle is the lead target joint of haemophilic arthropathy. These results are consistent with previous reports showing more haemarthroses and worse joint scores for ankles compared with knees or elbows in patients with haemophilia treated with prophylaxis or on demand . Based on our and other authors’ results, we suggest that ankles should be the joints of primary interest for monitoring treatment using MRI.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, higher MRI scores for the maximally affected ankle compared with the mean index joint in all patient subgroups and the scarcity of pathologic findings in knees of patients with normal ankles indicate that in most patients, the ankle is the lead target joint of haemophilic arthropathy. These results are consistent with previous reports showing more haemarthroses and worse joint scores for ankles compared with knees or elbows in patients with haemophilia treated with prophylaxis or on demand . Based on our and other authors’ results, we suggest that ankles should be the joints of primary interest for monitoring treatment using MRI.…”
Section: Discussionsupporting
confidence: 93%
“…The long-term effects on joints include limited range of motion (ROM), deformity, crippling disability, and chronic pain 3,4,1214. Studies have confirmed that patients with inhibitors experience greater ROM limitations and joint pain at an earlier age than those without inhibitors 3,4,15. Patients with high-titer inhibitors clearly demonstrate worse clinical and radiological joint scores than patients without inhibitors, and a three-fold increased risk of disability,3,4,12 due to more rapidly progressive joint disease 2,11,16…”
Section: Physical Impact Of Inhibitors In Patients With Hemophiliamentioning
confidence: 99%
“…Patients with inhibitors also have higher incidences of mobility-related problems,3,4,15,16 hospitalizations,3,4 school and work absenteeism,3 and difficulty maintaining a job,3 along with higher treatment costs, compared with patients without inhibitors3,44 (Table 1). As would be expected based on these factors, the QoL of patients with inhibitors is lower than for non-inhibitor hemophilia patients 4,12,13,33,45.…”
Section: Psychosocial Impact Of Inhibitors On Patients With Hemophiliamentioning
confidence: 99%
“…Similarly, van Dijk et al reported that during a median follow-up of 19 years, 35% of patients who discontinued prophylaxis at a median age of 21.5 years presented with similar median clinical scores and median Pettersson scores to patients who did not discontinue prophylaxis [18]. In contrast, data from the prospective US Hemophilia Growth and Development Study indicate that the impact of joint bleeding (manifested as a progression of joint disease) does not diminish with age [32]. Of 11 male haemophilia A or B patients who were at least 16 years of age at enrolment, 54.5% of those who had normal joints at entry developed abnormalities and 28.1% of normal joints at baseline became abnormal during a median of 7 years of follow-up, during which time the patients were typically receiving on-demand treatment.…”
Section: Discussionmentioning
confidence: 85%